Of another nature. (New York : Loughelton Gallery, 1988)
Birner, Rhona ; Celmins, Vija ; Chow, David ; Ess, Barbara ; Fish, Julia ; Gillette, Frank ; Harvey, Steven ; Krakovsky, Chere ; Morris, James ; Morrison, Richard ; Marsh, Georgia ; Nelson, Joan ; Phelan, Ellen ; Ramaseder, Josef
Of another nature, Loughelton Gallery, New York, may 1988
boek